2019
DOI: 10.1101/598771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complementing 16S rRNA gene amplicon sequencing with estimates of total bacterial load to infer absolute species concentrations in the vaginal microbiome

Abstract: Whereas 16S rRNA gene amplicon sequencing quantifies relative abundances of bacterial taxa, variation in total bacterial load between samples restricts its ability to reflect absolute concentration of individual species. Quantitative PCR (qPCR) can quantify individual species, but it is not practical to develop a suite of qPCR assays for every bacterium present in a diverse sample. We analyzed 1320 samples from 20 women with a history of frequent bacterial vaginosis, who self-collected vaginal swabs daily over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…This reinforces that even a model designed to account for the distribution of varying efficiencies cannot accurately predict the efficiency of an individual taxon when only relative abundance data are available. Note that these findings corroborate existing literature: Boshier et al (2019) found that BVAB2 spp. is a high-efficiency taxon, and McLaren et al (2019) found that G. vaginalis is a low-efficiency taxon.…”
Section: Leave-one-out Analysis To Predict Observed Qpcrsupporting
confidence: 92%
See 3 more Smart Citations
“…This reinforces that even a model designed to account for the distribution of varying efficiencies cannot accurately predict the efficiency of an individual taxon when only relative abundance data are available. Note that these findings corroborate existing literature: Boshier et al (2019) found that BVAB2 spp. is a high-efficiency taxon, and McLaren et al (2019) found that G. vaginalis is a low-efficiency taxon.…”
Section: Leave-one-out Analysis To Predict Observed Qpcrsupporting
confidence: 92%
“…While we did not find a reference to estimator (4) Boshier et al (2019) recently validated this proposal using taxon-specific qPCR primers and found it to be "predictive of absolute concentration with certain key exceptions," such as certain taxa and low biomass (low total bacterial concentration: q j=1 µ ij ) samples. Bonk et al (2018) give an excellent overview of sources of discrepancies between qPCR and 16S sequencing data.…”
Section: A Simple Efficiency-naïve Estimatormentioning
confidence: 81%
See 2 more Smart Citations
“…This yielded 401 unique ASVs in 629 samples, mapping to species (n=255; 63.6%), genus (n=116; 28.9%), or higher taxonomic level (n=30; 7.5%). Concentrations in cells/μl per ASV per sample were estimated by multiplying the ASV-specific copy-normalized relative abundance by the sample-specific 16S rRNA gene copies concentration 33,34 . Heatmaps of the 20 most common ASVs by sample are shown in Figure S1A for relative abundances and Figure S1B for concentrations.…”
Section: Methodsmentioning
confidence: 99%